Mechanical properties of tire replaced concrete / Khadijah Hamzah - Hamzah, Khadijah (2007)
This thesis present on the mechanical properties of tire replaced concrete. The effect on replacement of coarse aggregate by rubber tire was investigated in this study. Three different contents of rubber tire chips were used: 10%, 20% and 30%. There are three test has been undertaken which are workability test, compression test and flexural test in order to examine the mechanical properties of tire replaced concrete, cubes with dimension 150 x 150 x 150 mm were used for compressive strength and prisms with dimension 50 x 50 x 250 mm were used for flexural strength. The result on specimen which contained rubber tire was compared to control specimen result. The incorporation of these rubber tires in concrete exhibited a reduction in compressive and flexural strength according to the percentage of tire replaced.